Understanding the post-frac soaking process in multi-fractured shale gas-oil wells - Guo, Boyun; Philip Wortman (Capillarity, 2024)
Multi-stage hydraulic-fracturing horizontal wells has revolutionized today’s oil and gas industry. Post-frac fluid soaking is essential for improving productivity of shale oil-gas wells. Optimization of soaking time is an open problem to solve in the petroleum industry. Understanding the post-frac soaking process is vitally important for solving the puzzle. Analytical solutions were developed in this study to describe the spontaneous imbibition processes in shale matrix and shale cracks during fluid soaking. Solutions show that the imbibition distance is directly proportional to the square root of imbibition time and the imbibition velocity is inversely proportional to the square root of imbibition time. The rate of spontaneous imbibition in shale cracks is much faster than that in shale matrix. Therefore, the optimum time for post-frac fluid soaking was further analyzed on the basis of the imbibition in shale cracks only. The solution was combined with pressure fall-off data to formulate a mathematical method for predicting the post-frac fluid soaking time required for the fluid to reach the mid-point between two adjacent hydraulic fractures. A case study with Tuscaloosa Marine Shale data suggests that the front of fluid imbibition should propagate 4 meters in 2 weeks and to 6 meters in 4 weeks. These numbers may be considered as the optimum times of post-frac fluid imbibition if the shale swell effect is negligible. Future research should quantify the effects of shale swelling on spontaneous imbibition so that the information can be incorporated in the soaking model to fully describe the imbibition process for better prediction of well productivity. Document Type: Original article Cited as: Guo, B., Wortman, P. Understanding the post-frac soaking process in multi-fractured shale gas-oil wells. Capillarity, 2024, 12(1): 6-16. https://doi.org/10.46690/capi.2024.07.02